International Trends in Higher Education and Sustainability - McCowan, Tristan (International Higher Education, 2025)
<h3 id="sustainability-has-become-one-of-the-buzzwords-of-higher-education-in-recent-years-leading-to-a-raft-of-strategies-initiatives-and-even-rankings-however-there-are-significant-gaps-in-the-knowledge-base-with-research-focusing-mainly-on-curricular-interventions-and-campus-operations-and-the-changes-in-practice-have-often-been-superficial-in-order-to-fulfill-its-potential-in-addressing-the-socio-environmental-crisis-a-deeper-transformation-is-needed-in-the-universitys-role-as-a-knowledge-institution-and-in-its-relationships-with-society" data-pm-slice="1 1 []">Sustainability has become one of the buzzwords of higher education in recent years, leading to a raft of strategies, initiatives, and even rankings. However, there are significant gaps in the knowledge base, with research focusing mainly on curricular interventions and campus operations, and the changes in practice have often been superficial. In order to fulfill its potential in addressing the socio-environmental crisis, a deeper transformation is needed in the university’s role as a knowledge institution and in its relationships with society.